PENGENALAN EKONOMI DAN BISNIS ISLAM MELALUI PENDAMPINGAN PEDULI COVID-19 DI DESA GUNUNG BUNDER II, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Ria Kusumaningrum; Susi Melinasari; Muhammad Yaya Supriadi (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
The Covid-19 pandemic has hit the whole world including Indonesia, which is currently making the government establish policies for the public so that the Covid-19 outbreak does not spread and spread in Indonesia. People are required to comply with health protocols (such as wearing masks, washing hands and keeping their distance) so that the chain of spread of the Covid-19 virus in Indonesia can be broken and no longer infects the wider community in Indonesia. Under these circumstances, community service was carried out with Covid-19 Caring Assistance in Gunung Bunder II Village, Pamijahan District, Bogor Regency, which was carried out at the same time as an introduction to Islamic economics and business. The community is enthusiastic about Islamic economics and business which cannot be separated from Islamic beliefs as a perfect way of life that has been adhered to by the community so far.